DOES THE DISCLOSURE OF ISLAMIC CORPORATE SOCIAL RESPONSIBILITY, ISLAMIC CORPORATE GOVERNANCE, PROFITABILITY, AND BANK SIZE AFFECT TAX AVOIDANCE IN ISLAMIC COMMERCIAL BANKS IN INDONESIA? - Fahreza, Irgi Anggi; Fithria, Annisa (Ultimaccounting Jurnal Ilmu Akuntansi, 2023)
Abstract” This paper investigates the influence of Islamic Corporate Social Responsibility (ICSR), Islamic Corporate Governance (ICG), profitability, and bank size on tax avoidance in Islamic Commercial Banks in Indonesia. This paper introduces a novel perspective on the factors contributing to tax avoidance within Indonesia's Islamic finance framework. While the general notion of tax management is recognized, this study innovatively explores the intersection of Islamic principles, corporate governance, and tax practices, providing insights that have not been adequately explored in prior research. The study employs a panel data regression analysis, utilizing data from 13 Islamic Commercial Banks spanning 2017-2022, totaling 58 observations. This research approach enables an in-depth investigation into the relationships between ICSR disclosure, ICG, profitability, bank size, and tax avoidance. The empirical findings indicate that ICSR disclosure, the proportion of independent commissioners, and the audit committee positively influence tax avoidance practices. Conversely, the Sharia Supervisory Board and bank size negatively correlate with tax avoidance. Surprisingly, as measured by Return on Assets (ROA), profitability does not significantly impact tax avoidance decisions. This study underscores the intricate connections between Islamic corporate practices, governance structures, and tax avoidance strategies in Islamic Commercial Banks. The research highlights the significance of ICSR disclosure, corporate governance effectiveness, and the presence of religious oversight in shaping transparent and accountable tax practices. Furthermore, the research cautions against overreliance on profitability as a determinant of tax avoidance behaviors. Keywords: Bank Size; Islamic Corporate Governance, Profitability; Islamic Corporate Social Responsibility; Tax Avoidance